Self-care adjustment experiences of Filipino patients with permanent abdominal stoma - Tiburcio, Mark Anthony A.; Igna, Henri Joshua R.; Inocencio, Kyra Alexa P.; Macapagal, Pauline Anne M.; Pati, Grace Antonette F.; Urbiztondo, Godolivo
Management techniques done with patients having colorectal cancer include undergoing permanent colostomy. Recent investigations on patients with stoma measure quality of life but findings only a few provided narrative descriptions of self-care adjustments. We therefore decided to pursue a phenomenological research that aims to describe self-care adjustment experiences of Filipino patients with permanent abdominal stoma within a postoperative period of 48 to 72 hours and within seven days following discharge. Data from four participants were gathered through interviews and direct observation. Content analysis was patterned to Collaizzi’s Phenomenological Analytic Method and revealed 33 themes which were clustered into eight categories. Further description of the phenomenon was done through development of a conceptual framework, the Ostomates’ Self-Care Adjustment Model, illustrating the self-care adjustment of the participants using concepts from Roy's Adaptation Model. We determined that self-efficacy is the core concept which helps the participants adjust to a life of having an abdominal stoma. Our recommendations include (1) replicating the study using a longer time frame and more intervals, (2) developing a tool to measure self-care adjustment status of ostomates, (3) focusing nursing care to promote their self-efficacy, and (4) replicating the study to further improve, develop, validate, or modify the framework.